ADAPTING LOBBYING EXPERIENCE OF DEVELOPED DEMOCRACY COUNTRIES IN UKRAINE - Hazizov M. M. (Pressing Problems of Public Administration, 2016)
The article studies the lobbying experience of developed democracies and the terms of its implementation in Ukraine. Analyzed are the key points of legal regulatory basis of lobbying in developed democracies. such The accent is made on the necessity of development of balanced tools for regulation of interest groups activity in their legal in uence on state legislative bodies in Ukraine.